Mismatch between Supplies and Demands of Canal Water in a Major Distributary Command Area of the Nagarjunasagar Left Canal - Rao, B Krishna; Rajput, TBS (Journal of Agricultural Engineering, 2006)
A study was conducted in the command area of Guvvalagudem major distributary of the Nagarjunasagar Left Canal, Andhra Pradesh to determine weekly canal water supplies and demands and to examine if any imbalances between the two exist in the command area. It was concluded that most of the times canal supplies were lesser than the design capacity and there were wide gaps between weekly canal water demands and supplies. The mismatch between the annual supplies and the annual demands were lesser in magnitude (up to 20%) when compared to the weekly mismatches, which went up to 100% in some cases.